The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/586081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Germline features associated with immune infiltration in solid tumors

Abstract: 24Given the clinical success of immune checkpoint blockade (ICB) across a diverse set of solid 25 tumors, and the emerging role for different immune infiltrates in contributing to response to ICB, 26 a comprehensive assessment of the properties that dictate immune infiltrations may reveal new 27 biological insights and inform the development of new effective therapies. Multiple studies have 28 examined somatic and functional immune properties associated with different tumor infiltrates; 29 however, germline… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 65 publications
(73 reference statements)
0
24
0
Order By: Relevance
“…(E) Overlap between differentially regulated mRNA and proteins between Hot versus Cold and Warm versus Cold tumors, and eGenes downstream of cis-eQTLs and cis-pQTLs. Recent studies have suggested the importance of germline variants in the immune profiles of solid tumors (Lim et al, 2018;Shahamatdar et al, 2020;Tian et al, 2021). Among 319 cis-pQTLs (cis-regulating the cognate protein) identified in this study, only 38 were also cis-eQTLs (cis-regulating cognate RNA)(Table S6).…”
Section: Additional Resourcesmentioning
confidence: 99%
“…(E) Overlap between differentially regulated mRNA and proteins between Hot versus Cold and Warm versus Cold tumors, and eGenes downstream of cis-eQTLs and cis-pQTLs. Recent studies have suggested the importance of germline variants in the immune profiles of solid tumors (Lim et al, 2018;Shahamatdar et al, 2020;Tian et al, 2021). Among 319 cis-pQTLs (cis-regulating the cognate protein) identified in this study, only 38 were also cis-eQTLs (cis-regulating cognate RNA)(Table S6).…”
Section: Additional Resourcesmentioning
confidence: 99%
“…Tregs, and exhausted T cells. These gene markers had been reported in previous studies [22][23][24][25][26].…”
Section: Timer Database Analysismentioning
confidence: 57%
“…The JAK-STAT signaling pathway plays critical roles in cytokine receptors and can modulate the polarization of T helper cells. A recent report by Shahamatdar et al 46 analyzing germline variants in the TCGA cohort demonstrated that host genetics are associated with phenotypes that describe the immune component of the tumor microenvironment; they found one SNP associated with the amount of infiltrating follicular helper T cells; and 23 candidate genes, some of which are involved in cytokinemediated signaling. Our patient cohort supports prior findings that patients with greater TCR richness in the peripheral blood had improved survival compared with patients with less clonal richness [47][48][49] .…”
Section: Discussionmentioning
confidence: 99%